Taxonomic study on the subfamily Oedipodinae (Orthoptera: Acrididae) from district Skardu, Gilgit-Baltistan, Pakistan (Zoo Botanica, 2025)
Oedipodinae is the most species-rich and globally distributed subfamily of grasshoppers in the family Acrididae, with 63 known species in Pakistan. Members of this subfamily are of significant economic importance, as they are pests of both pasture lands and cultivated crops. In this study, we report 10 species including five subspecies under eight genera of the subfamily Oedipodinae, including Locusta Linnaeus, 1758, Pternoscirta Saussure, 1884, Gastrimargus Saussure, 1884, Scintharista Saussure, 1884, Heteropternis Stål, 1873, Sphingonotus Fieber, 1852, Helioscirtus Saussure, 1884, and Acrotylus Fieber, 1853, from district Skardu, Gilgit-Baltistan, Pakistan. The digital photographs, diagnosis, and regional distribution data of these known species from Pakistan are presented.
Keywords: Band-winged grasshoppers; checklist; migratory locust; Northern areas